Application of Transformer Heat Circuit Model in Power Substation Station Area. Issue 3 (July 2021) - Hou, Zhe; Lv, Xinliang; Yang, Bo; Liu, Hao; Liu, Shulin; Yu, Changlong
Abstract: The hot spot temperature of transformers operating in the station area is calculated in real-time using the transformer heat path model as it is impossible to measure the internal winding hot spot temperature directly and modifying the transformer will increase the cost. The smart distribution transformer terminal is an important device for collecting and processing data on the side of the distribution transformer, with a container built from Linux inside to run an application (App) with specific functions developed in the Linux environment. Based on that, the heat circuit model of the transformer is developed into an App installed into the container of the smart distribution transformer terminal to realize the function of the real-time computing and warning of transformer hot spot temperature. It is expected to provide some reference for the transformer operating normally and stably.